Independence Relationship to Police Member Performance of Poso Police Station - Rahmadhani Antu; Annisa Warastri (Publikasi Indonesia, 2024)
This study aims to analyze the relationship between independence and the performance of police members. The research approach carried out is quantitative. The data collection technique in this study is a list of questions (questioner). Data was collected through a questionnaire distributed to 155 respondents who were members of the Poso Police. In this study, the results of the analysis showed that there was a significant positive relationship between independence and performance. So, it can be said that there is a relationship between independence and performance. The findings of this study highlight the importance of independence for individual performance. The suggestions that can be given to agencies are that they can be a reference to increase the independence of members in order to improve the performance of their members.